Innovations and Challenges in Intermediate Respiratory Care Units: Toward Effective Integration into the Hospital System - Beatriz Jara Chinarro; Laura Pazos Rodriguez; Miguel Cuchí Alfaro; Ainhoa Izquierdo Pérez; Silvia Aguado Ibañez; María Churruca Arrospide; Marta Soler Vigil; Cristina Moral; Carlos Almonacid (Open Respiratory Archives)
This review gives a comprehensive and nuanced appraisal of the current state of Intermediate Respiratory Care Units (IRCUs). It aims to evaluate the distribution of IRCUs in Spain, identify challenges and gaps in the current system and analyze the impact of IRCUs during the COVID-19 pandemic.A review of the evolution and current state of IRCUs was conducted. A search was performed on PubMed. Original articles were selected for analysis. Additionally, recommendation documents on IRCUs from SEPAR and other Scientific Societies were reviewed. The review analyzes the history and evolution of the IRCUs, their role and function, IRCU models, the evolution of admission criteria, and their efficacy and efficiency.IRCUs offer significant benefits by improving patient outcomes through accurate categorization and specialized treatment of severe pulmonary diseases, ensuring high-quality care. They reduce ICU admission rates, resulting in substantial cost savings for hospitals.Our analysis indicates that while IRCUs contribute positively to patient outcomes and resource optimization in Spain, there are significant challenges related to heterogeneity in unit structures, staffing, and resource allocation. Standardizing definitions and models may enhance the effectiveness and comparability of IRCUs across the healthcare system. Resumen: Esta revisión ofrece una valoración completa y matizada del estado actual de las unidades de cuidados respiratorios intermedios (UCRIs). Pretende evaluar la distribución de las UCRI en España, identificar los desafíos y las brechas en el sistema actual, y analizar el impacto de las UCRIs durante la pandemia de COVID-19.Se realizó una revisión de la evolución y estado actual de las UCRIs. Se realizó una búsqueda en PubMed. Se seleccionaron artículos originales para su análisis. Además, se revisaron documentos de recomendaciones sobre UCRIs de la SEPAR y otras sociedades científicas. La revisión analiza la historia y la evolución de las UCRIs, su papel y función, los modelos de UCRIs, la evolución de los criterios de ingreso y su eficacia y eficiencia.Las UCRIs ofrecen beneficios significativos al mejorar los resultados de los pacientes mediante una categorización precisa y un tratamiento especializado de las enfermedades pulmonares graves, garantizando una atención de alta calidad. Reducen las tasas de ingreso en las UCI, lo que supone un ahorro sustancial de costes para los hospitales.Nuestro análisis indica que, si bien las UCRIs contribuyen positivamente a los resultados de los pacientes y a la optimización de los recursos en España, existen desafíos importantes relacionados con la heterogeneidad en las estructuras de las unidades, la dotación de personal y la asignación de recursos. La estandarización de definiciones y modelos puede mejorar la eficacia y la comparabilidad de las UCRIs en todo el sistema sanitario.